Antenatal diagnosis of alobar holoprosencephaly: a case report - Waikar, Manjushri; Singh, Anamika (International Journal of Contemporary Pediatrics, 2019)
Holoprosencephaly (HPE) is a structural malformation of the brain that results from the complete or incomplete noncleavage of the forebrain/ prosencephalon of the embryo into 2 hemispheres1. We present a case of twenty-five year-old primigravida presented to the Outpatient department of Obstetrics for routine checkup and diagnosed with Alobar holoprosencephaly on 2nd level USG. Fetal MRI was performed and the findings were confirmed. Even though ultrasonography is diagnostic in the detection of fetal anomalies, MRI plays a vital role due to its multiplanar capability and excellent soft tissue resolution. The purpose of publishing this case is to sensitize the clinicians to the classical features of holoprosencephaly on various imaging modalities and to stress the importance of its detection before 20 weeks of gestation so as to allow for legal medical termination and alleviate maternal psychological trauma of bearing a deformed fetus.